ҲУҚУҚ ТАЪЛИМИДА МАТНЛИ ЎҚУВ МАТЕРИАЛЛАРИНИНГ ВИЗУАЛ-МЕТОДИК ТАЪМИНОТИДАН ФОЙДАЛАНИШ ТЕХНОЛОГИЯСИ – ПЕДАГОГИК МУАММО - Кудайбергенова, Т.К.; Бекбергенова, Г.С.; Ибодуллаева, И.Н. (SCIENCE and SOCIETY, 2021)
This article discusses the technology of using and methodological support of textual teaching materials in the teaching process of law in schools of the Republic of Uzbekistan as a pedagogical problem, creating methodological supply, its necessity and consequences.